FOREST FIRE RISK ASSESSMENT USING GIS AND AHP INTEGRATION IN BUCAK FOREST ENTERPRISE, TURKEY - Coban, H. O.; Erdin, C. (ALOKI Applied Ecological Research and Forensic Inst Ltd, 2020)
Forest fires create an increasingly severe and negative impact on ecosystem services such as carbon storage, climate balancing and water supply as a result of global warming threatening our planet. One of the steps to fight forest fires is to perform a risk assessment. Forest fire risk assessment allows the identification of locations at high risk of forest fire and estimate its sphere of influence. In this way, it provides decision-making support to the fire-fighting organization The purpose of this study was to conduct a forest fire risk assessment in forests located in Bucak Forest Enterprise in Turkey that is vulnerable to fire at the first degree. In the study, the weights of the criteria that lead to fire risk were computed with Analytic Hierarchy Process (AHP). The risk classes of the criteria were exported to the raster layer of the Geographical Information System (GIS). The results showed that 25% of forests in Bucak region were at high risk, while 32% were at medium fire risk. We believe that the approach adopted in this study may contribute to forest fire risk assessments and risk mapping of Mediterranean forest ecosystems that have similar climate, topographic structure and vegetation.
Keywords: Mediterranean forests; fire risk factors; fire risk mapping; spatial analysis; fire sensitivity; ANALYTIC HIERARCHY PROCESS; FUZZY AHP; LAND SUITABILITY; NATIONAL FOREST; DECISION; IMPACT; AGGREGATION; SEVERITY; MODEL; Environmental Sciences & Ecology